Reconfiguring Local Criminalization: Constitutional Implications of The New Indonesian Criminal Code For Regional Autonomy - Fauzani, Muhammad Addi; Putra, Alamsyah Nurahmad; Mahmuda, Rahmadina Bella (Jurnal Hukum IUS QUIA IUSTUM, 2026)
The enactment of the new Penal Law has removed the authority of local governments to prescribe criminal sanctions in local regulations, raising constitutional concerns regarding the implementation of local autonomy. This study aims, first, to examine how the penal amendments affect the implementation of local autonomy and, second, to formulate short-term and long-term legal policies that local governments should adopt in response to the elimination of this authority. This research employs normative legal research using statutory and conceptual approaches. The findings reveal that Articles 613 and 615 of the Penal Law are inconsistent with the constitutional principle of regional autonomy guaranteed under Article 18 paragraphs (5) and (6) of the Constitution, as well as the Law on the Formation of Legislation and the Local Government Law. These provisions reflect a centralized legislative policy that weakens local autonomy by limiting the authority of local governments to formulate criminal sanctions. In the short term, local governments should strengthen the enforcement of administrative sanctions to ensure compliance with local regulations. In the long term, Articles 613 and 615 should be repealed to restore the constitutional authority of local governments to prescribe criminal sanctions through local regulations. Such restoration should be accompanied by strengthening the institutional capacity of local law enforcement agencies, particularly the Civil Service Police Unit, and improving correctional facilities to support the effective implementation of local criminal law. This study contributes to the discourse on the constitutional balance between criminal law codification and regional autonomy in Indonesia.